Exploring the Lesson Study Experience of EFL Instructors at Higher Education: A Pilot Study - İlknur Bayram; Fatma Bıkmaz (Anı Publishing, 2018)
This study aims to present the findings of a pilot Lesson Study implementation at a Turkish foundation university which took place between May and June, 2016 with the participation of three EFL instructors. Since an in-depth analysis of a group of instructors was required in order to have a comprehensive understanding of how the model was implemented, what issues and challenges were experienced and what lessons were learned by participant instructors, the study was designed as a qualitative phenomenological case study. Data obtained through interviews were subsequently coded and interpreted through content analysis. Results showed that issues with Lesson Study were mainly about feelings of anxiety, workload, conceptualizing the model and performing the model; however, results also revealed that it could contribute to professional development of instructors in certain aspects such as collaborative lesson planning, delivering less teacher-fronted lessons, focusing more on students and improving time management skills.